Energy and exergy analyses of skipped cycle mode in a single-cylinder engine fuelled with diesel and natural gas - Tuncer, Erdal; Dogan, Battal; Sandalci, Tarkan; Erol, Dervis (INDERSCIENCE ENTERPRISES LTD, 2022)
In this study, performance and exhaust emissions were examined experimentally at different engine loads (25%, 50%, and 75%) at a constant speed of 1,500 rpm using pure diesel before modifications and pure natural gas (NG100) after modifications. Furthermore, experimental studies were conducted under 2 normal-1 skipped cycle (2N1S) and 3 normal-1 skipped cycle (3N1S) conditions using pure natural gas as a fuel in a converted spark-ignition engine. In the present study, energy and exergy analyses were performed using the performance and exhaust emission values obtained from experiments. As a result of the energy analysis, effective thermal efficiency values of 39.46% and 34.37% were found in diesel and natural gas fuels, respectively, at an engine load of 75% without cycle skipping. It was observed that the effective thermal efficiency value reached the maximum value of 35.99% in case of cycle skipping in natural gas and at an engine load of 50%.
Keywords: natural gas; skipped cycle; pollutant emissions; energy analysis; exergy analysis; SPARK-IGNITION ENGINES; COMBUSTION; INJECTION; PERFORMANCE; STRATEGIES; CNG; EMISSIONS; Thermodynamics; Energy & Fuels